Luminescent phosphate glass ceramic capable of quickly responding to radiation dose detection as well as preparation method and application of luminescent phosphate glass ceramic
By preparing Dy3+ ion-doped NaBaPO4 glass ceramics, the problems of harsh growth conditions or toxicity of existing OSL materials have been solved, and rapid response radiation dose detection performance has been achieved, which is suitable for the fields of luminescence and radiation dose detection.
Patent Information
- Application Number
- CN202511286730.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-10
- Publication Date
- 2025-12-19
AI Technical Summary
Existing OSL materials such as Al2O3:C and BeO have problems such as harsh crystal growth conditions or toxicity, and the radiation dose detection performance of NaBaPO4 glass ceramics has not been studied. There is a need to develop new non-toxic materials with low phonon energy and good luminescence performance.
Using Na2CO3, BaCO3, NH4H2PO4 and H3BO3 as raw materials, Dy3+ ion-doped NaBaPO4 glass ceramics were prepared by mixing, melting and quenching, grinding, pressing and molding and heat treatment, forming three shallow trap energy levels of different depths to achieve fast response performance.
It achieves a good linear dose response in the range of 0.1-200 Gy, has a fast signal readout time and bleaching capability, and is suitable for the fields of luminescence and radiation dose detection.
Smart Images

Figure CN121159142A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of phosphate fluorescent glass ceramics, and particularly relates to a luminescent phosphate glass ceramic for detecting radiation dose in a fast response mode and a preparation method and application thereof. BACKGROUND
[0002] Optically Stimulated Luminescence (OSL) successfully converts invisible radiation into visible light signals by emitting light signals proportional to the absorbed ionizing radiation energy (X, beta and gamma rays, etc.) when the material is properly stimulated by light. This technology is widely used in medical field, environmental sediment dating and nuclear emergency dose monitoring. Currently, the commercially available OSL materials are Al2O3:C and BeO. However, the former has harsh crystal growth conditions, and the latter is toxic and needs to be modified before use. Therefore, researchers are exploring new OSL materials, including fluorescent powder, glass, single crystal, ceramic, etc. Among them, borophosphate glass with a formula of Na2CO3-BaCO3-NH4H2PO4-H3BO3 has better luminescent performance, lower phonon energy, better thermal stability, non-toxic material and simple preparation as a matrix for rare earth ions. At the same time, Dy 3+ can directly emit white light at a specific excitation wavelength, and the emitted light has a spectral gap from the excitation light, effectively avoiding signal crosstalk, which is an ideal dual-function luminescent center. There is no research on the radiation dose detection performance of NaBaPO4 glass ceramic, and for the above reasons, NaBaPO4 glass ceramic is selected as the matrix of Dy 3+ to study its luminescence and radiation dose characteristics. SUMMARY
[0003] The present application aims at the deficiencies of the prior art, and provides a luminescent phosphate fluorescent glass ceramic for detecting radiation dose in a fast response mode, a preparation method and application thereof. The material is prepared by mixing, grinding, calcining, melting, quenching, grinding, pressing and forming, and heat treatment and cooling of Na2CO3, BaCO3, NH4H2PO4 and H3BO3, and Dy 3+ is doped in the form of a compound in the glass ceramic matrix, i.e. Dy 3+The ion-doped NaBaPO4 glass ceramic emits cold white light under excitation at a specific excitation wavelength. Through experiments and calculations, it is found that the sample contains three different shallow trap levels with different depths. This characteristic gives the sample significant fast response performance. During the optical excitation reading process, the charge carriers can be rapidly released, thereby achieving shorter signal reading time and fast bleaching ability, and achieving good linear dose response to high-energy radiation in the range of 0.1-200Gy. The sample has good white light emission characteristics, fast response characteristics, wide radiation dose response performance and good reusability, and can be used as a new type of fluorescent material in the fields of luminescence and radiation dose detection.
[0004] The luminescent phosphate glass ceramic for fast response radiation dose detection is prepared from Na2CO3, BaCO3, NH4H2PO4 and H3BO3 in terms of mole percentage. 3+ The molar percentage of the doped dysprosium-containing compound in the total raw material concentration is 0.1-1.0. The specific operation is performed according to the following steps:
[0005] a. Na2CO3 31-40.9%, BaCO3 23-26%, NH4H2PO4 13-16%, H3BO3 23-26% in terms of mole percentage, and 0.1-1.0% of Dy2O3 are added and ground in a mortar for 1-2h to obtain a mixture, and then the mixture is transferred to a corundum crucible;
[0006] b. The corundum crucible containing the mixture in step a is placed in a muffle furnace with a temperature of 1250-1350℃ and calcined for 1-4h, and then the high-temperature melt is poured on a steel plate for quenching to obtain a glass;
[0007] c. The glass obtained in step b is broken and ground in an agate mortar for 2-3h to obtain a glass powder;
[0008] d. The glass powder obtained in step c is placed in a hydraulic press to press into a round sheet at a pressure of 15-30kgf / cm 2 for 20-60s;
[0009] e. The round sheet obtained in step d is heat treated at a temperature of 450-580℃ for 3-6h to obtain a luminescent phosphate glass ceramic sheet with three different shallow energy level traps of 0.60-0.67eV, 0.42-0.46eV and 0.71-0.79eV.
[0010] A preparation method of a luminescent phosphate glass ceramic for fast response radiation dose detection is performed according to the following steps:
[0011] a. Take Na2CO3 31-40.9%, BaCO3 23-26%, NH4H2PO4 13-16%, H3BO3 23-26% by mole percentage, dope 0.1-1.0% of Dy2O3, and place in a mortar for 1-2h of grinding and mixing, to obtain a mixture, and then transfer the mixture to a corundum crucible;
[0012] b. Place the corundum crucible containing the mixture in step a in a muffle furnace at a temperature of 1200-1300℃ for calcination for 2-4h, then pour the high-temperature melt on a steel plate for quenching process to obtain a glass;
[0013] c. Crush the glass obtained in step b and place it in an agate mortar for 2-3h of grinding to obtain a glass powder;
[0014] d. Place the glass powder obtained in step c in a hydraulic press to press into a round sheet at a pressure of 15-30kgf / cm 2 for 20-60s of pressure holding time;
[0015] e. Heat treat the round sheet obtained in step d at a temperature of 450-580℃ for 3-6h of heat treatment time to obtain a luminescent phosphate glass ceramic sheet with three different depths of shallow level traps 0.60-0.67eV, 0.42-0.46eV and 0.71-0.79eV.
[0016] The obtained luminescent phosphate glass ceramic sheet emits cold white light under excitation at an excitation wavelength of 350nm.
[0017] The obtained luminescent phosphate glass ceramic sheet realizes a shorter signal readout time and a shorter bleaching time of 230-250s.
[0018] The obtained luminescent phosphate glass ceramic CW-OSL dose response is linearly fitted in the range of 0.1-200Gy, with R 2 =0.9984.
[0019] The luminescent phosphate glass ceramic for rapid response radiation dose detection, its preparation method and application, which are described in the present application, use raw materials Na2CO3, BaCO3, NH4H2PO4, H3BO3 and Dy2O3 as raw materials, to obtain a Dy 3+Ion-doped NaBaPO4, which has NaBaPO4 nanocrystals precipitated. The glass ceramic material has high crystallinity and transparency, and its excitation spectrum is in the visible light region, which can realize cold white light emission under excitation at a certain excitation wavelength. Experiments and calculations show that the sample contains three different shallow trap energy levels, which endow it with significant fast response performance. Specifically, during the light excitation reading process, the charge carriers can be rapidly released, thereby realizing shorter signal reading time and fast bleaching ability. Meanwhile, the appropriate doping amount of Dy 3+ The sample of the present application has good white light emission characteristics, fast response characteristics, wide radiation dose response performance and good reusability, and can be applied as a new type of fluorescent material in the fields of light emission and radiation dose detection.
[0020] The fast response radiation dose detection luminescent phosphate glass ceramic and its preparation method and application provided by the present application adopt a glass (mol%) Na2CO3-BaCO3-NH4H2PO4-H3BO3 glass matrix, wherein NH4H2PO4 and H3BO3 provide a matrix environment with high hardness, good mechanical properties, low phonon energy and excellent thermal stability; the introduction of Na2CO3 and BaCO3 is necessary for successfully precipitating NaBaPO4 crystals.
[0021] The fast response radiation dose detection luminescent phosphate glass ceramic and its preparation method and application provided by the present application have good luminescent properties, low phonon energy and high thermal stability, and have the characteristics of non-toxicity, simple preparation process, uniform luminescence and enhanced OSL signal response as a matrix of rare earth ions. Cold white light can be emitted under excitation at a specific wavelength; through analysis of trap composition, it is found that the charge carriers can be rapidly released during the light excitation reading process, thereby realizing shorter signal reading time and fast bleaching ability; the linear fitting R 2 =0.9984 in the range of 0.1-200 Gy of high-energy rays can be realized.
[0022] Compared with the prior art, the present application has the following advantages:
[0023] 1、The present application obtains a glass ceramic containing NaBaPO4 nanocrystals through a melting quenching method and a controlled temperature crystallization heat treatment method, and the glass ceramic has better luminescent properties, lower phonon energy and better thermal stability, is a good matrix of rare earth ions, has low molding temperature and low raw material cost, and the doping amount of Dy 3+The introduction of Dy can make the sample emit cool white light at a specific excitation wavelength, while the introduction of Ce can make the sample emit blue light at a specific excitation wavelength. 3+ The glass can be embedded into a low phonon energy environment, which is beneficial to improve the OSL light intensity, reduce the non-radiative transition probability, and improve the light emission efficiency.
[0024] 2, the luminescent phosphate glass ceramic of the application, after high-energy ray irradiation, studies the OSL curve, and analysis shows that the sample has three different depths of shallow trap energy levels, and the characteristics give the sample significant fast response performance, which is specifically manifested as that, in the light excitation reading process, the charge carriers can be rapidly released, so that shorter signal reading time and fast bleaching ability are realized; the linear fitting R 2 =0.9984 of the high-energy ray in the range of 0.1-200 Gy can be realized. BRIEF DESCRIPTION OF DRAWINGS
[0025] Figure 1 (a) is the DSC curve of the glass in Example 1 of the application, and (b) is the XRD spectrum of the glass ceramic after heat treatment in Examples 1, 2, 3 and 4 of the application;
[0026] Figure 2 (a) is the SEM image of the fluorescent glass ceramic in Example 2 of the application, and (b) is the EDS element distribution map of the fluorescent glass ceramic in Example 2 of the application;
[0027] Figure 3 (a) is the excitation spectrum of the fluorescent glass ceramic in Examples 1, 2, 3 and 4 of the application, and (b) is the emission spectrum of the fluorescent glass ceramic in Examples 1, 2, 3 and 4 of the application, and the inset is the CIE 1931 chromaticity coordinate;
[0028] Figure 4 (a) is the continuous wave OSL decay curve (470nm excitation, 1Gy beta irradiation) and the fitting component of the fluorescent glass ceramic in Example 3 of the application, and (b) is the CGCD deconvolution of the TL glow curve (1Gy beta irradiation, 5K / s) of the fluorescent glass ceramic in Example 3 of the application and the experimental-fitting residual error;
[0029] Figure 5 is the optical bleaching curve of the fluorescent glass ceramic in Example 3 of the application under the sun simulator (1Gy beta irradiation, 240s complete erasing);
[0030] Figure 6 is the dose response relationship of the fluorescent glass ceramic in Example 4 of the application (0.1-200Gy beta irradiation, R 2 =0.9984);
[0031] Figure 7OSL signal reusability (10 cycles, 1 Gy beta irradiation) of the fluorescent glass-ceramics in Example 4 of the present application, inset is the relative standard deviation (RSD = 1.11%) of the peak intensity;
[0032] Figure 8 Dose linearity of the fluorescent glass-ceramics in Example 4 of the present application, inset is the linear fit of the integrated OSL intensity versus dose (R 2 = 0.9976, 1.0 - 5.5 Gy beta irradiation);
[0033] Figure 9 OSL curves of the NaBaPO4 glass-ceramics with different Dy 3+ concentrations in Example 3 of the present application (1 Gy beta irradiation), inset is the integrated intensity peak at 0.25 mol% concentration;
[0034] Figure 10 Application schematic of the fluorescent glass-ceramics in Example 4 of the present application;
[0035] Figure 11 OSL and TL schematic of the fluorescent glass-ceramics in Example 4 of the present application. DETAILED DESCRIPTION
[0036] The technical solutions of the present application will be described in detail below in combination with the drawings and examples.
[0037] Example 1
[0038] a. Take Na2CO3 32%, BaCO3 26%, NH4H2PO4 16%, H3BO3 26% by mole percentage, do not dope Dy2O3, and place in a mortar for 1 h of thorough grinding and mixing to obtain a mixture, and then transfer the mixture to a corundum crucible;
[0039] b. Place the corundum crucible containing the mixture in step a in a muffle furnace at a temperature of 1200℃ for calcination for 2 h, and then pour the high-temperature melt on a steel plate for quenching to obtain a glass;
[0040] c. Crush the glass obtained in step b and place in an agate mortar for thorough grinding for 2 h to obtain a glass powder;
[0041] d. Pour 0.20 g of the glass powder obtained in step c into a mold with a diameter of 8 mm, and place in a hydraulic machine to press into a disc under a pressure of 15 kgf / cm 2 ;
[0042] e. Heat treat the disc obtained in step d at a temperature of 480, 520, 540, 560℃ for 4 h, and finally naturally cool to room temperature.
[0043] The DSC curve of the glass powder obtained in step (c) is shown in Figure 1 (a), and the XRD pattern of the fluorescent glass-ceramic obtained in step (e) is shown in Figure 1 (b). The temperature of heat treatment is determined according to the glass transition temperature and the crystallization peak temperature in the DSC curve.
[0044] Example 2
[0045] a, Na2CO3 40.75%, BaCO3 23%, NH4H2PO4 13%, H3BO3 23% by mole percentage, doped with 0.25% of Dy2O3, and placed in a mortar for grinding and mixing for 2 h to obtain a mixture, and then the mixture is transferred to a corundum crucible;
[0046] b, the corundum crucible containing the mixture in step a is placed in a muffle furnace at a temperature of 1250°C for calcination for 3 h, and then the high-temperature melt is poured on a steel plate for quenching to obtain a glass;
[0047] c, the glass obtained in step b is crushed and placed in an agate mortar for grinding for 3 h to obtain a glass powder;
[0048] d, 0.18 g of the glass powder obtained in step c is poured into a mold with a diameter of 10 mm, and pressed into a disc by a hydraulic press at a pressure of 20 kgf / cm 2 for 30 s;
[0049] e, the disc obtained in step d is subjected to heat treatment at a temperature of 500°C for 4 h, and finally naturally cooled to room temperature to obtain a luminescent phosphate glass-ceramic disc with three different depths of shallow level traps of 0.60-0.67 eV, 0.42-0.46 eV, and 0.71-0.79 eV.
[0050] The SEM image of the fluorescent glass-ceramic obtained in step e is shown in Figure 2 (a), and the element distribution on the surface of the glass-ceramic is shown in Figure 2 (b). The results show that the NaBaPO4 crystals are uniformly distributed in the glass matrix, and Dy 3+ is successfully introduced without element segregation. The excitation spectrum and the emission spectrum of the fluorescent glass-ceramic are shown in Figure 3 (a) and 3(b), respectively, both of which show the characteristic excitation and emission peak positions of Dy 3+ doped NaBaPO4 glass-ceramic. The OSL curve and the TL curve of the fluorescent glass-ceramic after irradiation of 1 Gy β rays are shown in Figure 4(a) and 4(b) shown, after fitting the two, it is indicated that there are three different traps in the sample; the fitting parameters obtained after fitting the OSL curve show that the fast decay parameter of the material is faster than that of other materials, and the data are shown in Table 1:
[0051] Table 1
[0052]
[0053] The fast response characteristics of the sample are proved. The results of the bleaching time study of the sample are shown in Figure 5 , and the faster bleaching time also proves the fast response characteristics of the sample; the linear response curve of the fluorescent glass ceramic to high-energy rays is shown in Figure 6 ; the results of repeated OSL tests on the sample are shown in Figure 7 ; and the sensitivity test of the sample to high-energy rays is shown in Figure 8 .
[0054] Example 3
[0055] a. Take Na2CO3 36%, BaCO3 25%, NH4H2PO4 13%, H3BO3 25.9% by mole percentage, dope 0.1% of Dy2O3, and place in a mortar for 2h of grinding and mixing, obtain the mixture, and then transfer the mixture to a corundum crucible;
[0056] b. Place the corundum crucible containing the mixture in step a in a muffle furnace with a temperature of 1280℃ and calcine for 4h, then pour the high-temperature melt on a steel plate for quenching process, and obtain the glass;
[0057] c. Crush the glass obtained in step b and place it in an agate mortar for 2h of grinding, and obtain the glass powder;
[0058] d. Pour 0.17g of the glass powder obtained in step c into a mold with a diameter of 12mm, and press into a disc under the pressure of 25kgf / cm 2 in a hydraulic machine, and the pressure holding time is 50s;
[0059] e. Heat treat the disc obtained in step d at a temperature of 520℃ for 3h, and finally naturally cool to room temperature, and obtain the luminescent phosphate glass ceramic disc with three different depths of shallow level traps 0.60-0.67eV, 0.42-0.46eV and 0.71-0.79eV.
[0060] The OSL curves of the fluorescent glass ceramic samples doped with different Dy 3+ after irradiation of 1Gy β rays are shown in Figure 9 .
[0061] Example 4
[0062] a, take Na2CO3 34.25%, BaCO3 24%, NH4H2PO4 15%, H3BO3 26% by mole percentage, doped with 0.75% of Dy2O3, and placed in a mortar for 1.5h of grinding and mixing, to obtain a mixture, and then transfer the mixture to a corundum crucible;
[0063] b, place the corundum crucible containing the mixture in step a in a muffle furnace at a temperature of 1300℃ for calcination for 4h, then pour the high-temperature melt on a steel plate for quenching process to obtain a glass;
[0064] c, break the glass obtained in step b and place it in an agate mortar for 3h of grinding to obtain a glass powder;
[0065] d, take 0.10g of the glass powder obtained in step c and pour it into a mold with a diameter of 14mm, and place it in a hydraulic machine to press into a disc under a pressure of 30kgf / cm 2 for 60s of pressure maintaining time;
[0066] e, heat treat the disc obtained in step d at a temperature of 580℃ for 6h of heat treatment time, and finally naturally cool to room temperature to obtain a luminescent phosphate glass ceramic disc with three different depths of shallow level traps 0.60-0.67eV, 0.42-0.46eV, and 0.71-0.79eV.
[0067] The schematic diagram of the sample obtained in step e is shown in Figure 10 .
[0068] Example 5
[0069] a, take Na2CO3 34%, BaCO3 24%, NH4H2PO4 15%, H3BO3 26% by mole percentage, doped with 1.0% of Dy2O3, and placed in a mortar for 1.5h of grinding and mixing, to obtain a mixture, and then transfer the mixture to a corundum crucible;
[0070] b, place the corundum crucible containing the mixture in step a in a muffle furnace at a temperature of 1300℃ for calcination for 4h, then pour the high-temperature melt on a steel plate for quenching process to obtain a glass;
[0071] c, break the glass obtained in step b and place it in an agate mortar for 3h of grinding to obtain a glass powder;
[0072] d, take 0.10g of the glass powder obtained in step c and pour it into a mold with a diameter of 14mm, and place it in a hydraulic machine to press into a disc under a pressure of 30kgf / cm 2The pressure is applied to press the material into a round disc, and the pressure holding time is 60 seconds.
[0073] e. The disc obtained in step d is heat-treated at 580℃ for 6 hours, and then allowed to cool naturally to room temperature to obtain luminescent phosphate glass-ceramic discs with shallow energy level traps of 0.60-0.67eV, 0.42-0.46eV, and 0.71-0.79eV.
[0074] The schematic diagrams of the OSL and TL of the sample obtained in step e are as follows: Figure 11 As shown. The significant difference between the undoped and doped samples is that the doped sample Dy 3+ As a luminescent center, it can emit cold white light under excitation light. After being irradiated, the doped sample can generate OSL and TL under thermal and light excitation.
[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to the embodiments, those skilled in the art should understand that modifications or equivalent substitutions to the technical solutions of the present invention do not depart from the spirit and scope of the technical solutions of the present invention.
Claims
1. A luminescent phosphate glass-ceramic for rapid response radiation dose detection, characterized in that, The luminescent phosphate fluorescent glass-ceramic is composed of Na₂CO₃, BaCO₃, NH₄H₂PO₄, and H₃BO₃ by molar percentage, and Dy is doped into the glass-ceramic matrix in the form of a compound. 3+ The dysprosium-containing compound doped in the raw materials accounts for 0.1-1.0 molar percentages of the total raw material concentration. The specific operation is carried out according to the following steps: a. Weigh out 31-40.9% Na2CO3, 23-26% BaCO3, 13-16% NH4H2PO4, and 23-26% H3BO3 according to molar percentage, dop with 0.1-1.0% Dy2O3, and grind and mix them thoroughly in a mortar for 1-2 hours to obtain a mixture. Then transfer the mixture to a corundum crucible. b. Place the corundum crucible containing the mixture from step a into a muffle furnace at a temperature of 1250-1350 ℃ and calcine for 1-4 h. Then pour the high-temperature molten material onto a steel plate for quenching to obtain glass. c. Crush the glass obtained in step b and grind it thoroughly in an agate mortar for 2-3 hours to obtain glass powder; d. Place the glass powder obtained in step c into a hydraulic press at a pressure of 15-30 kgf / cm³. 2 The pressure is applied to press the material into round discs, and the pressure holding time is 20-60 seconds. e. Heat-treat the discs obtained in step d at a temperature of 450-580 ℃ for 3-6 h to obtain luminescent phosphate glass-ceramic discs with shallow energy level traps of 0.60-0.67 eV, 0.42-0.46 eV, and 0.71-0.79 eV at three different depths.
2. A method for preparing a luminescent phosphate glass-ceramic for rapid response radiation dose detection, characterized in that, Follow these steps: a. Weigh out 31-40.9% Na2CO3, 23-26% BaCO3, 13-16% NH4H2PO4, and 23-26% H3BO3 according to molar percentage, dop with 0.1-1.0% Dy2O3, and grind and mix them thoroughly in a mortar for 1-2 hours to obtain a mixture. Then transfer the mixture to a corundum crucible. b. Place the corundum crucible containing the mixture from step a into a muffle furnace at a temperature of 1200-1300 ℃ and calcine for 2-4 h. Then pour the high-temperature molten material onto a steel plate for quenching to obtain glass. c. Crush the glass obtained in step b and grind it thoroughly in an agate mortar for 2-3 hours to obtain glass powder; d. Place the glass powder obtained in step c into a hydraulic press at a pressure of 15-30 kgf / cm³. 2 The pressure is applied to press the material into round discs, and the pressure holding time is 20-60 seconds. e. Heat-treat the discs obtained in step d at a temperature of 450-580 ℃ for 3-6 h to obtain luminescent phosphate glass-ceramic discs with shallow energy level traps of 0.60-0.67 eV, 0.42-0.46 eV, and 0.71-0.79 eV at three different depths.
3. The application of the luminescent phosphate glass ceramic for rapid response radiation dose detection as described in claim 1 or 2 in the preparation of cold white light emitted under excitation wavelength of 350 nm.
4. The use according to claim 3, characterized in that, The obtained luminescent phosphate glass-ceramic sheet achieves a shorter signal readout time and a shorter bleaching time of 230-250s.
5. The use according to claim 3, characterized in that, The obtained luminescent phosphate glass-ceramic CW-OSL dose response was linearly fitted in the range of 0.1-200 Gy, R0. 2 =0.9984.